Using Theory of Interpersonal Behaviour to Predict Usage Behaviour of Government to Citizen ICT Services among people Affected by the war - H. Abdulrahman, Saifuldeen; Sakira Binti Kamaruddin, Siti; Bt Othman, Nafishah (International Journal of Engineering and Technology, 2018)
As ICT developments profoundly promoted fields such as government to citizen services and disaster management, there is an absent of framework and study to clarify the factors that influence the usage behaviour of the services among people affected by a non-natural disaster. A conceptual framework is developed in this research to measure such factors underpinned on the Theory of Interpersonal behaviour. This paper presents the first phase of this research. Literature review is conducted, investigated issue is recognized. Hypotheses and conceptual framework, as well as the research methodology are also described in this paper. Lastly, contribution, limitation and conclusion are also included.
Keywords: Disaster; G2C ICT services; TIB; Usage behaviour; War environment.